Monetary Policy and Asset Price Overshooting: A Rationale for the Wall/Main Street Disconnect - CABALLERO, RICARDO J.; SIMSEK, ALP (Journal of Finance, 2024)
ABSTRACT We analyze optimal monetary policy and its implications for asset prices when aggregate demand has inertia. If there is a negative output gap, the central bank optimally overshoots aggregate asset prices (above their steady‐state levels consistent with current potential output). Overshooting leads to a temporary disconnect between the performance of financial markets and the real economy, but accelerates the recovery. When there is a lower bound constraint on the discount rate, good macroeconomic news is better news for asset prices when the output gap is more negative. Finally, we document that during the COVID‐19 recovery, the policy‐induced overshooting was large.